ChemInform Abstract: Rhodium(III)‐Catalyzed Indazole Synthesis by C—H Bond Functionalization and Cyclative Capture. Issue 44 (14th October 2013) - Lian, Yajing; Bergman, Robert G.; Lavis, Luke D.; Ellman, Jonathan A.
Abstract Regioselectivity of the reaction is mainly controlled by the steric effects of the aromatic substituent at nitrogen [cf.